2005
DOI: 10.1152/ajpgi.00036.2004
|View full text |Cite
|
Sign up to set email alerts
|

The female intestine is more resistant than the male intestine to gut injury and inflammation when subjected to conditions associated with shock states

Abstract: . The female intestine is more resistant than the male intestine to gut injury and inflammation when subjected to conditions associated with shock states. Am J Physiol Gastrointest Liver Physiol 288: G466 -G472, 2005. First published October 21, 2004; doi:10.1152/ajpgi.00036.2004.-Having documented that proestrus female rats are more resistant to shock-induced acute gut and hence lung injury than male rats, we tested the hypothesis that the female gut is more resistant to injury and produces less of an inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
84
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 41 publications
4
84
0
8
Order By: Relevance
“…It is noteworthy that, in contrast with the antiinflammatory effect of a direct NOAEL exposure in OVX rats, the same dose administered to pregnant and lactating mothers resulted in opposite effects in female offspring in adulthood. It is also remarkable that this deleterious impact was observed during estrus, i.e., at a time of the reproductive cycle when the colon of adult females is more resistant to injury, and produces less proinflammatory cytokines when challenged by experimental inflammation, as a result of a protective influence of plasma estrogen dominance (22,28). Our results clearly show that the endocrine disruptor effects of BPA vary depending on age of the gut, and that a perinatal exposure has a long-term effect on mucosal immune defenses that predisposes female offspring to enhanced proinflammatory responses in the colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that, in contrast with the antiinflammatory effect of a direct NOAEL exposure in OVX rats, the same dose administered to pregnant and lactating mothers resulted in opposite effects in female offspring in adulthood. It is also remarkable that this deleterious impact was observed during estrus, i.e., at a time of the reproductive cycle when the colon of adult females is more resistant to injury, and produces less proinflammatory cytokines when challenged by experimental inflammation, as a result of a protective influence of plasma estrogen dominance (22,28). Our results clearly show that the endocrine disruptor effects of BPA vary depending on age of the gut, and that a perinatal exposure has a long-term effect on mucosal immune defenses that predisposes female offspring to enhanced proinflammatory responses in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several lines of clinical and experimental evidence have reported that estrogens are involved in the development and regulation of the gut barrier. Altogether, a sex difference in intestinal permeability and inflammation (22), the prevalence of irritable bowel syndrome in women (23), the fluctuations of irritable bowel syndrome-associated abdominal pain in women during their menstrual cycle (24), as well as the wide expression of estrogen receptors (ERs) in human fetal and adult colonic mucosa (25,26) suggest that estrogens play a key role. In animal studies, estrogen action on intestinal permeability, inflammation, and viscerosensitivity are controlled by ERs in gut epithelial cells and sensory neurons, the latter conveying peripheral information to the central nervous system (27)(28)(29).…”
mentioning
confidence: 99%
“…From a different point of view, female Wistar rats have been reported to be more resistant to lethal circulatory stress induced by trauma or intestinal ischemia (Homma et al 2005;Deitch et al 2008). Furthermore, Offner et al (1999) identified male gender as an independent risk factor for the development of severe infection in surgical patients.…”
mentioning
confidence: 99%
“…In contrast, estrogen concentrations rise, often markedly (5,7,36,48). Studies in rodent models suggest that these opposing changes in serum androgen and estrogen levels may be adaptive in critical illness and may decrease morbidity and mortality (2,11,14,15,19,20,30,35,37,38,62,65). However, this phenomenon has been difficult to study prospectively in humans.…”
mentioning
confidence: 99%